Truth Telling in Peacebuilding: A Buddhist Contribution - Ngoc Bich Ly Le (International Journal of Interreligious and Intercultural Studies, 2021)
Truth telling has been recognized as important in the process of trauma healing and reconciliation according to modern peacebuilding theories. Studies have shown that truth telling is not a simple issue but involves problems and challenges that need research and solutions. This study contributes to this problem-solution or the question â€œHow should difficult and painful truth be told in a way that minimizes harm and maximizes benefit for all?â€ by offering an alternative knowledge and method rooted in the Buddhist tradition. Based on textual study of the Majjhima Nikaya and Anguttara Nikaya, the paper argues that the Buddhaâ€™s teachings can widen the understanding and minimize potential problems with the work of truth telling whether in the collective or interpersonal context by providing a concrete systematic framework and criteria for reflection, making decision and communication of truth.